Implementation of Algebra Structure in The Field of Biology in Blood Group Inheritance - Sri Hastuti; Ellis Mardiana Panggabean (Journal of Education and Teaching Learning, 2023)
Genetics is a branch of biology that scientifically studies heredity (heredity). One of the inherited genetic identities is blood type. The most commonly used blood group systems are the ABO and Rhesus blood group systems. This blood group inheritance can be analyzed using any antigen from the blood group system. The antigei are then used as the basis for the vector space affecting the field. Binary operations were defined for each blood group system and analyzed using gamete and zygotic algebra. We derive equations that are used as axioms to form the algebraic structure of any blood group system. After the ABO blood group and Rhesus algebra were determined, the ABO binary function was determined and supplemented with the Rhesus blood group system (ABOi Rh). This binomial operation is used to derive equations that act as axioms to form the algebraic structure of the ABO Rh blood group system.